Bosutinib for Successful Treatment‐Free Remission in Chronic Myeloid Leukemia - Yuki Fujioka; Maiko Abumiya; Takaaki Ono; Naoto Takahashi (Cancer Medicine, 2025)
ABSTRACT Introduction and Objective This study explored the status of patients with chronic myeloid leukemia following the safe discontinuation of frontline or second‐line bosutinib treatment. The goal was to assess the long‐term outcomes and factors influencing treatment‐free remission (TFR) following cessation of bosutinib therapy. Methods The median duration of bosutinib treatment among 16 patients was 48 months. All patients achieved a deep molecular response before bosutinib discontinuation, which was sustained for a median pre‐cessation period of 27 months. Patients were monitored for molecular response and clinical outcomes. Results After bosutinib discontinuation, the major molecular response was lost in six patients: within 6 months in five patients and at 19 months in one patient. All six patients achieved a major molecular response after at least 3 months of bosutinib re‐treatment. Ten patients exhibited successful TFR without loss of major molecular response for a median duration of 48 (16–101) months. Kaplan–Meier analysis revealed a 68.8% treatment‐free survival at 12 months. After bosutinib cessation, eight patients developed Grade 1–2 withdrawal syndrome. No differences were observed in the clinical characteristics or bosutinib treatment between patients with TFR at 12 months (TFR group) and those without remission (recurrence group), except for the deep molecular response duration before bosutinib cessation (31 vs. 24 months, p = 0.009). T‐cell profiling using flow cytometry revealed a higher percentage of effector memory CD8+ T cells at 1 and 3 months after bosutinib discontinuation in the TFR group than in the recurrence group (p = 0.012 and p = 0.005, respectively). Conclusion Bosutinib can be safely discontinued under certain conditions, similar to other tyrosine kinase inhibitors. Additionally, T‐cell profile analysis before and after bosutinib discontinuation may predict successful TFR.